Resolving Students’ Disruptive Behavior: Learning from the Experience of Indonesian Pre-service Teachers - Nasution, Ulfa Rayhani; Ani, Rahmah Fithri (Journal of Disruptive Learning Innovation (JODLI), 2023)
Disruptive behavior is one of the factors that can hinder the success of learning.  Hence, disruptive behavior must be identified and handled for the learning process to function smoothly. This study has two objectives: (1) to identify EFL students’ disruptive behavior during the learning process, and (2) to investigate the strategies employed by pre-service teachers to reduce it. This case study used qualitative research approach. Class observation and in-depth interviews with 10 pre-service teachers were used to gather the data, which were later analyzed using Thematic Content Analysis. The results reveal that students’ disruptive behavior includes classroom diversion, aggressive behavior, and frittering away. To address this issue, the preservice teachers employed a number of strategies, including rewards provision, establishing class norms, giving motivation, incorporating students' hobbies and extracurricular interests into classroom activities, and supervising students to prevent disruptive behavior. This study is hoped to add insight and provide an overview of solving student’s disruptive behavior for pre-service teachers as a provision for teaching practicum.